PELATIHAN SISTEM JURNAL BERPASANGAN BAGI SISWA SMA HARAPAN JAYA - Yanti; Anggraini, Bella; Suroso, Audrey Felicia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Based on the results of the interview with teachers, there is a problem where currently Harapan Jaya High School class 12 students majoring in science only get a little accounting material at school. Therefore, the solution offered by the PKM Team is to conduct training on the topic